Aplasia cutis congenita associated with epidermolysis bullosa in a Nigerian child - Ochigbo, Sunday O.; Kingsley, Anachunna I.; Antigha, Cobham E.; Jacob, Udo J. (International Journal of Research in Dermatology, 2018)
Aplasia cutis congenita (ACC) associated with epidermolysis bullosa is a rare heterogeneous congenital cutaneous lesion characterized by absence of skin mostly involving the epidermis and dermis. ACC commonly affect the scalp in 75% of cases but can affect other sites like the trunk and limbs. It is highly heterogeneous and inherited either as autosomal dominant, recessive or caused by a new mutation. The exact cause is unknown although some intrauterine conditions may play a role in the etiology. Anticonvulsants and antithyroid drugs have also been implicated. The condition can coexist with other syndromes. Our patient was 2.95 kg female baby delivered via emergency caesarean section (CS) due to previous CS and cephalopelvic disproportion (CPD) at gestational age (GA) of 42 weeks. After delivery, we observed skin defects which measured 6 cm×4 cm and 2 cm×2.5 cm on the shin and dorsum of the right foot respectively. There were loose fragment of skin and blisters around the hypopigmented edges of the lesion. Milia were observed on the dorsum of the foot; hence patient was classified into group VI Friedens classification of ACC. The lesion was conservatively managed and dressed daily using gauze-impregnated with honey. The lesion healed within 2 weeks and 4 weeks review showed no residual scar. We recommend conservative management with honey in the absence of deep tissue loss as observed in our patient, as well as educate parents on the need to avoid aggravating factors.